The influence of leadership values on culture values: a Structural Equation Modelling (SEM) approach (Pengaruh nilai kepimpinan ke atas nilai budaya: suatu pendekatan pemodelan persamaan berstruktur) - Zainol Mustafa,; Mohd Rashid Ab Hamid,; Nur Riza Mohd Suradi,; Fazli Idris,; Mokhtar Abdullah,; Abdullah Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2011)

(untitled)
﻿The importance of core values that upheld the leadership and cultures are very well- understood and these criteria are important in determining the organisational success. Thus, this article examines the impact of leadership onto the organisational culture through value- based indicators. The study was conducted at one of the universities in the East Coast of Malaysia. An instrument was developed and adapted from previous study and pilot tested. 400 questionnaires were administered to the respondents resulting of 153 questionnaires were returned. The data were coded in Predictive Analytics Software (PASW) version 18.0 and AMOS software was used to analyse the hypothesised model using Structural Equation Modelling (SEM) approach. The result of the modelling suggests that the revised hypothesised model yields a fit statistics that are adequate with p-value = 0.078, CFI = 0.99, GFI = 0.967, TLI = 0.980 and RMSEA = 0.075. In conclusion, the revised model fits the data well and there is no proof that the model is incorrect based on the fit statistics. Implications of the study was significant to enhance and empower value-based leadership approach that influenced the university’s culture towards achieving success and excellence.